Klaim Rumah Sakit Kepada BPJS Kesehatan Berkaitan Dengan Rawat Inap Dengan Sistem INA– CBGs - Suhartoyo Suhartoyo (Administrative Law and Governance Journal, 2018)
This study aims to find out the hospital problem for the body organizing the health service (BPJS) with INA-GBGs system. The research method used in this research is normative law research, using a written approach (legal approach), and conceptual approach (conceptual approach), then after that analysis using site analysis. The database analysis base uses primary data and secondary data that allows the author of the data needed directly through the literature and the literature. The results showed that the compilation of the Ministerial Regulation no. 27 of 2014 concerning the basics of the Indonesian case base system and Permenkes No. 28 of 2014 concerning Guidelines for the Implementation of the National Health Insurance Program. This is due to the availability of equipment for the payment of Hospital to BPJS which berorintasi on the frequency of health professions in the Hospital, through the sorting and classification of the hospital.Keywords: hospital claims, BPJS, inpatient With INA-GBGs system